A novel DOPO derivative containing multifunctional groups aiming to improve fire safety, thermal stability and curing state towards epoxy resin. (November 2022) - Guo, Yong; Rong, Hu; Chen, Zhongwei; Chen, Tingting; Yu, Yuan; Zhang, Xida; Chu, Yanpeng; Zhang, Qingwu; Li, Changxin; Jiang, Juncheng
Highlights: A reactive DOPO-based flame retardant PABO was synthesized by a one-step method. The CN bond in PABO can react with the -OH formed after opening the ring of EP to form a crosslinked structure and improve the transparency of the composite. Less addition and excellent flame retardant performance. Abstract: A novel reactive flame retardant (PABO) was synthesized via a one-pot reaction from para-aminobenzonitrile, p-hydroxy benzaldehyde and 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and applied on epoxy resin (EP). The curing state of the EP mixture with the addition of PABO was excellent as detected by the cure index (CI). Thermogravimetric analysis showed that compared with DOPO, PABO possessed a higher degradation temperature, a lower thermal decomposition rate and the Char800 (char residues at 800°C) increased from 1.5 to 26.5 wt%. The EP/PABO-5 with only 5 wt% PABO content attained a limiting oxygen index of 32.7% and possessed the UL-94 V-0 level. The calculated flame retardant index (FIGRA) showed that the fire safety of EP/PABO-5 was superior to that of EP/DOPO-5. For flame retardant mechanism, in the gas phase, PABO possessed the function of retarding the thermo-oxidative decomposition of EP, the quenching effect of phosphorus radicals and the diluting effect of non-combustible nitrogen-containing gas. In the condensed phase, the trimerization reaction of nitrile groups happened and the existence of the phosphaphenanthrene group together promoted the formation of a stable char layer, which could obstruct the transfer of heat and oxygen.